2009
DOI: 10.3390/v1030574
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Innate Immunity by Paramyxovirus Accessory Proteins

Abstract: Paramyxovirinae, a subfamily of Paramyxoviridae, are negative strand RNA viruses comprised of many important human and animal pathogens, which share a high degree of genetic and structural homology. The accessory proteins expressed from the P/V/C gene are major factors in the pathogenicity of the viruses, because of their ability to abrogate various facets of type I interferon (IFN) induction and signaling. Most of the paramyxoviruses exhibit a commonality in their ability to antagonize innate immunity by bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Viruses utilize a number of strategies for counteracting immune and apoptotic signals. Previous studies have demonstrated that paramyxoviruses can use the accessory proteins from the P/V/C gene to inhibit apoptosis [ 33 , 34 ]. The V protein of mumps virus is also known to block IFN expression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Viruses utilize a number of strategies for counteracting immune and apoptotic signals. Previous studies have demonstrated that paramyxoviruses can use the accessory proteins from the P/V/C gene to inhibit apoptosis [ 33 , 34 ]. The V protein of mumps virus is also known to block IFN expression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incapacity of RSV to fully inhibit SG formation, in contrast to MV and SeV, might reflect the lack of expression of the C protein from the RSV genome. In the context of SeV or MV infection, the C protein that results from the translation from an alternative overlapping open reading frame of the P gene [ 12 ], is mainly responsible for interference with SG formation [ 55 , 61 , 62 ]. In contrast to wt viruses, MV or SeV mutants deleted for the C protein expression are strong inducers of G3BP1-positive SG formation.…”
Section: Rsv Takes Advantage Of Cytoplasmic Sgs and Specific Ibsmentioning
confidence: 99%
“…As shown in Figure 6A , the ErbB3 promoter activity was increased in HBx-expressing cells in a dose-dependent manner, indicating that HBx transcriptionally increased ErbB3 gene expression. HBx has been reported to activate various transcription factors such as AP-1, NF-κB, and CREB [ 51 53 ]. By using JASPAR database, the putative transcription factors binding to ErbB3 promoter were predicted (Figure 6B ), and among them Sp-1, NF-κB, AP1, E2F1, and HNF4α have been reported to be activated in response to HBx expression [ 54 58 ].…”
Section: Resultsmentioning
confidence: 99%